The Cake Application: A Mobile-Assisted Language Learning (MALL) to Improve English Speaking Skill - Nurbaiti Ali (ASIAN PUBLISHER, 2023)
Speaking is typically a crucial component of the English unit since it allows students to express and communicate their thoughts and opinions. Possessing strong communication skills allows students to discover who they are during the teaching-learning process. As a result, in order to encourage and assist the students, the teacher must determine the best way to spark their interest and enhance their proficiency in learning English. The excellent and contemporary Cake application can be utilized as supplementary material for speech classes. It encourages engaged and joyful learning among the pupils in the classroom. With the Cake application, they can concentrate more on honing their speaking skills and don't have to worry about making mistakes when they practice speaking because the app provides immediate feedback. Cake application also supports students in learning vocabulary. They can gain more vocabulary by learning dialogues from Cake application.